Accumulation solaire : la théorie des systèmes-mondes de The Expanse - Brent Ryan Bellamy; Sean O’Brien (ReS Futurae)
The Syfy television series The Expanse (2015-) transposes a form of combined and uneven development from Earth to the solar system, making the human reality of life lived in space a central concern. The Expanse envisions a colonized solar system, replete with a United-Nations-controlled Terra and Luna, a military dictatorship on Mars, and a densely populated asteroid belt. This essay proposes that The Expanse offers an image of a worlds-system, by which we mean an interplanetary system of capital accumulation that reproduces the structure of twentieth-century geopolitical economy at the level of the solar system. At one and the same time, The Expanse imagines a new cycle of accumulation founded in the planetary system and premised on ecological crisis on Earth and it provides a re-narration of the end of the cycle of accumulation that has been called the long twentieth century or the American century, which exasperated the climate crisis in the first instance. The Expanse is a pivotal narrative that promises a new interplanetary cycle of accumulation and its decline all at once, a fantasy of continuity that simultaneously dramatizes the contemporary crisis of futurity.